Biochemical Changes of Saliva in patients with Radiotherapy in comparison to healthy subjects - Mohammed, Faris Jabaz; Yassir, Alaa Dakhil; Nadhir Jebur, Ahmed (Research journal of pharmacy and technology, 2023)
Background: radiotherapy for the treatment of head and neckcancer can produce damage to tissue and specifically salivary glands, causing an alteration in composition of saliva accompanied with oral mucositis. The present study was designed to investigate the changes in saliva components before and after irradiation in comparison to control. Methods: Sixty human male participate in this study. Thirty of them were patients with head and neck cancer prior to and after radiotherapy were evaluated for constituents of saliva and compared with other thirty free of cancer as a control group. Collection of 2ml of stimulated saliva with biochemical analysis of (buffering capacity, salivary amylase and salivary total protein) were done for all subjects. Results: the current findings show an increment in salivary flow rate for irradiate patients compared to control. while reduction in buffer capacity was observed in irradiate patient in comparison to control. Results for both salivary amylase and salivary total protein illustrated a reduction in their concentration before and after irradiation in comparison to control with significant difference value. Conclusion: Radiotherapy affects salivary glands causing alteration in biochemical components of saliva and may cause oral tissue damage.